2016
DOI: 10.3389/fpls.2016.01053
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Treatments with a Protein-Based Resistance Inducer Partially Modify Phyllosphere Microbial Communities of Grapevine

Abstract: Protein derivatives and carbohydrates can stimulate plant growth, increase stress tolerance, and activate plant defense mechanisms. However, these molecules can also act as a nutritional substrate for microbial communities living on the plant phyllosphere and possibly affect their biocontrol activity against pathogens. We investigated the mechanisms of action of a protein derivative (nutrient broth, NB) against grapevine downy mildew, specifically focusing on the effects of foliar treatments on plant defense s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…In grapevine, the role and composition of leaf microbial communities were largely ignored until recently, when the concept of microbial terroir started to spread [40,41]. For example, the grapevine can potentially host more than 80 different viral species, of which only about half are recognized as agents of economic relevant diseases [42][43][44]. For most of these viral entities, the effects and metabolic modifications caused in grapevine are still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In grapevine, the role and composition of leaf microbial communities were largely ignored until recently, when the concept of microbial terroir started to spread [40,41]. For example, the grapevine can potentially host more than 80 different viral species, of which only about half are recognized as agents of economic relevant diseases [42][43][44]. For most of these viral entities, the effects and metabolic modifications caused in grapevine are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For most of these viral entities, the effects and metabolic modifications caused in grapevine are still unknown. However, mutualistic interactions have been reported, in which some viruses conferred drought tolerance and increased resistance to downy mildew (Plasmopara viticola) [30,43,44]. Thus, grapevine-virus interactions can be studied not only according to classical host-pathogen relationships but also by considering grapevine and its viruses as a single micro-ecosystem able to adapt to the surrounding environment and to influence plant responses, including those to fungi and fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, artificial protein hydrolysates were demonstrated to act as resistance inducers [25][26][27] and their biocontrol activity was affected by the original protein source, hydrolysis method and degree of hydrolysis [20,28], as well as by their biochemical properties [18,56]. On the basis of these findings, we investigated and compared the impact of different plant protein sources and different hydrolysis methods on the efficacy of protein hydrolysates in controlling courgette powdery mildew, in order to clarify the possible role of specific peptide fragments and amino acids Our results showed that both enzymatic and acid methods significantly enhanced the efficacy of guar against courgette powdery mildew, in particular when hydrolysis was carried out with Alcalase 50% and with H 2 SO 4 6N condition B, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, guar enzymatic hydrolysates did not affect conidia germination on leaf disks, suggesting a mode of action mainly based on the stimulation of plant resistance mechanisms, as observed for other protein extracts. Indeed, peptide fragments of different origin have been shown to elicit grapevine defence mechanisms by the up-regulation of defence-related genes [24][25][26][27]. However, further analysis will be required to demonstrate how these peptide sequences could be involved in plant immunity regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation